Os princípios e limites metafísicos do estado jurídico em Kant - CARDOSO, Victor Moraes (Universidade Federal do Pará, 2015)
This dissertation sets in a bibliographic research, of an analytical, critical and reflective nature about an epistemological universe that encompasses the principles and metaphysical boundaries of the Legal State in Kant, which addresses the rational grounds, as immutable and universal archetypes, of the Legal State, from what Immanuel Kant teaches in his Doctrine of Right. With this guideline and considering the misinterpretations of the fundamental principles of law, preliminarily, outline some divergent conceptions of the said project, which are 'rejected' in the course of this dissertation. Then it explains the role played by reason in the theoretical and practical purposes, with the aim of fixing the locus occupied by a Moral System in Practical Philosophy. This system consists of two subdivisions, namely Ethics and the Law. Thus, it is established law as a practical science, with its concept. And yet, it discusses the theme of freedom, which pervades the entire path taken in the development, its relation to practical reason, as well as the distinction that exists between will and freedom of choice. These considerations allow subsequently characterize the law, but without forgetting to distinguish it from the Ethics. Also can explain the principle and the universal law of the Right as criteria of legitimacy and justice, law and principle that refer to freedom of choice within which coercion is presented as an analytical element. The accountability is another issue addressed, which presupposes the idea of freedom, whose absence would deprive the law of all meaning. Thus, it follows the private law, arguing it until reaching its premise, whereby it is possible to get right on any object outside the freedom of choice. It examines, instead, the institutes of Private Law, say, the Right in rem, Personal rights and the Personal Rights of in rem character. Is entered, then, the Public Law, presenting the Legal State as guarantor of rights that are pre-existing. On this track, going up to the formal requirements of the State, which is the tripartition of powers and their relationships. Other points for the Legal State are also addressed, such as citizenship and its relationship to state power, the alleged right of revolution, the duty to reform the Civil Constitution, the Right to Punish. It is noteworthy that try to overcome a difficulty that is not addressed in any written consulted: the accountability of public officials. However, the shape of the Legal State is also addressed. Moreover, spin up some lines to individual and social rights and their relationship to the fundamentals of law. Anyway, after all trodden path, it appears that Legal State is a duty imposed by practical reason - an end in itself which runs from metaphysical principles - ones who can offer us an unchanging model and irreplaceable State.